In situ investigations of failure mechanisms of silica fibers from the venus flower basket (Euplectella Aspergillum). (May 2023) - Morankar, Swapnil K.; Mistry, Yash; Bhate, Dhruv; Penick, Clint A.; Chawla, Nikhilesh
Abstract: The fibers of the deep-sea sponge Euplectella aspergillum exhibit exceptional mechanical properties due to their unique layered structure at a micrometer length scale. In the present study, we utilize a correlative approach comprising of in situ tensile testing inside a scanning electron microscope (SEM) and post-failure fractography to precisely understand mechanisms through which layered architecture of fibers fracture and improves damage tolerance in tensile loading condition. The real-time observation of fibers in the present study confirms for the first time that the failure starts from the surface of fibers and proceeds to the center through successive layers. The concentric layers surrounding the central core sacrifice themselves and protect the central core through various toughening mechanisms like crack deflection, crack arrest, interface debonding, and fiber pullout. Statement of significance: Biological materials often exhibit multiscale hierarchical structures that can be incorporated into the design of next generation of engineering materials. The fibers of deep-sea sponge E. aspergillum possess core-shell like layered architecture. Our in situ study reveals astounding strategies by which this architecture delays the fracture of the fiber. The core-shell architecture of these fibers behaves like fiber-reinforced ceramic matrix composite, where the outer shells act as a matrix and the central core acts as a fiber. The outer shells take the environmental brunt and scarify themselves to protect the central core. The precise understanding of damage evolution presented here will help to design architected materials for load-bearing applications. Graphical abstract: Image, graphical abstract